The Theme of Vintage in the Pictorial Traditions of Late Antiquity, Early Christianity, and in the Art of Sasanian Iran - Mikayelyan, Lilit Sh. (Actual Problems of Theory and History of Art, 2016)
There are a number of themes in Late Antique and Early Christian art, which are also known in the art of Sasanian Iran. Among them is the scene of grape harvest. The study and comparative analysis of the given theme in the context of three above mentioned cultural traditions have not received a necessary attention among the researchers; therefore it needs a special investigation.Scenes of grape harvest first appeared in ancient art and were connected with the cult of Dionysus. In the Late Antique and Early Christian periods they were often depicted on the pavement and wall mosaics of Rome and East Roman provinces, as well as on the marble sarcophagus. In Christian tradition, the scenes of grape harvest were reinterpreted according to the Christian symbolic traditions, where wine became the symbol of the atonement and the sacrament of the Eucharist.In Early Medieval Armenian art the theme of “grape harvest” is known from the 6th–7th centuries’ relief from Dvin, and the facade of the Church of St. Cross in Akhtamar (10th century). In the art of Sasanian Iran, it is found on silver vessels and dishes of the 6th–7th centuries. In these scenes, as well as in Early Christian mosaics, the brunches of grapes are of huge sizes; they are often half height of human and animal gures. is iconographic detail which is common both for Sasanian Iran and for Christian monuments underlines the allegorical character of the scenes which were based on the symbolic image of the Heavenly Paradise.
Keywords: Armenia; early medieval sculpture; antiquity; vintage; bear; Sasanian toreutics